Flower specialization of butterflies and impacts of non-native flower use in a transformed tropical landscape. (September 2016) - Jain, Anuj; Kunte, Krushnamegh; Webb, Edward L.
Abstract: Flower -feeding ecology of tropical butterflies remains poorly studied, particularly in transformed landscapes, despite that flower availability and quality affect important life-history traits and are critical to butterfly abundance. We recorded 190 butterfly species feeding on 149 flowering plant species across forests and urban parks in Singapore. Butterflies were classified as flower generalists, intermediates or specialists by fitting a power function between the number of flower species utilized and the flower visits observed for that butterfly species. Generalized least squares models were constructed between the degree of flower specialization and traits of butterfly species. Our analysis showed that more species were flower generalists than flower specialists in both habitat types. Forty-three percent of feeding observations in forested sites were on non-native flowers. Yet, flower specialists used significantly higher proportions of native flower species in their diet than flower generalists and tended to be forest dependent. Some forest butterflies were critically dependent (> 70%) on single native flower species. Out of 19 butterfly species examined for response across habitats, five expanded their diet but six contracted their diet with urbanization. The regression models revealed that adult conspicuousness, habitat breadth, proboscis length, and wingspan were most strongly associated with flower specialization when accounting for phylogenetic relatedness. Our results suggest that while landscape transformation in the tropics could benefit some flower-generalist butterflies by providing extra resources, flower-specialist butterflies could further increase dependence on few native flower sources. Such butterflies may require intervention in terms of landscape management of their preferred flower resources. Highlights: Data on flower specialization of tropical butterflies is lacking Impact of habitat transformation on flower use of butterflies was examined Flower specialists used significantly higher proportions of native flower species Traits associated with flower specialization were identified Flower specialist butterflies may require landscape management of flower resources